Structural Biology of PrP Prions - Stubbs, Gerald (Cold Spring Harb Perspect Med, 2017)
Prion diseases are characterized by the deposition of amyloids, misfolded conformers of the prion protein. The misfolded conformation is self-replicating, by a mechanism solely enciphered in the conformation of the protein. Because of low solubility and heterogeneous aggregate sizes, the detailed atomic structure of the infectious isoform is still unknown. Progress has, however, been made, and has allowed insights into the structural and disease-related mechanisms of prions. Many structural models have been proposed, and a number of them support a consensus trimeric β-helical model, significantly more complex than simple amyloid models. There is evidence that such complexity may be a necessary property of prion structure. Knowledge of the structure of prions will provide a greater understanding of the protein isoform conversion mechanism, and could eventually lead to rationally designed intervention strategies.